The Effect Of Promotion, Quality Products, And Price On Purchase Decisions - Junita Ari Angraini (Journal of World Conference (JWC), 2019)
This study aims to analyze whether promotion, product quality, and price have a significant effect on consumer purchasing decisions on screen printing Convocation of Surabaya City. This research is quantitative research. Population and sample distributed were 107 respondents. Data collection techniques using a questionnaire. Analysis of the data used is using multiple linear regression analysis techniques and classical assumption tests. Based on the results of the study show that the price variable has a positive and significant effect on purchasing decisions with a tcount = 2.074> of ttable 1.983 with a significance of 0.041 <0.05 which means significant, and for product quality variables on purchasing decisions shows tcount = 5.968> from ttable1,983 with a significance of 0,000 <0,05 which means significant, the price of purchasing decisions shows a value of tcount = 3,091> of ttable 1,983 with a significance of 0,003 <0,05 which means significant.